Lean Compendium Introduction to Modern Manufacturing Theory - Rüttimann, Bruno G. (Springer International Publishing, 2018)
The book covers basic manufacturing theory and develops a Cartesian approach to explaining lean. It provides a structured fundament how a lean manufacturing system works. Students get a consistent approach, explaining lean by increased complexity (mono-product, multi-product, complex manufacturing systems) with theorems, corollaries, and lemmas. Instructors get explanations for lean based on a systemic model, helping to transmit a clear view about the theory of lean.